Packaging materials and packages
Patent Information
- Application Number
- JP2021203696
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-15
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-12-15
AI Technical Summary
【0008】 本発明の包装材料は、良好な熱接着性を有し、且つ耐油性に優れ、さらに環境負荷が小さい。
Smart Images

Figure 0007640935000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging material utilizing a heat sealing method and a package using the same. [Background technology]
[0002] Heat seal sheets are widely used as packaging materials for food, medicines, industrial products, etc. Examples of usage include self-adhesive heat seal sheets made into bags, heat seal sheets attached to other substrates, and lid materials for molded containers such as cups and blister packs.
[0003] In addition to heat sealing properties, heat seal sheets are sometimes required to have various barrier properties depending on the contents to be packaged. In particular, when packaging food, oil resistance is often required. For example, Japanese Patent Application Laid-Open No. 2015-155582 (Patent Document 1) and Japanese Patent Application Laid-Open No. 2020-183593 (Patent Document 2) have proposed packaging materials with paper-based heat seal properties and oil resistance. These use petrochemical materials such as styrene-styrene-butadiene copolymer latex, olefin resins, and acrylic resin emulsions to obtain heat sealability and oil resistance, and have not given sufficient consideration to the environmental impact. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-183593 A [Patent Document 2] JP 2015-155582 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a packaging material that has excellent heat sealability and oil resistance while reducing the amount of petrochemical materials used, and to solve environmental problems such as marine pollution. [Means for solving the problem]
[0006] The inventors have thoroughly investigated the use of non-petrochemical materials that have a small environmental impact as raw materials, and as a result have discovered that by using casein or a salt thereof in a heat seal layer and setting the internal bond strength of the packaging material within a specific range, a heat seal sheet having good heat sealability, oil resistance, and other properties can be obtained, thereby arriving at the present invention.
[0007] The present invention has the following aspects. [1] A packaging material having a coating layer on at least one side of a substrate, the coating layer containing 30 to 100% by mass of casein and / or a salt thereof, and the internal bond strength of the packaging material measured in accordance with JAPAN TAPPI 18-2 is 200 J / m 2 A packaging material characterized by the above. [2] The coating layer wax The packaging material according to [1], [3] The packaging material according to [1] or [2], wherein wood pulp is used as the raw material for the base material. [ 4 The wood pulp has a beating degree according to Canadian Standard Freeness of 150 mLCSF or more and 500 mLCSF or less. [3] The packaging material described. [ 5 The substrate contains a styrene-(meth)acrylic acid copolymer compound and / or a styrene-maleic anhydride copolymer compound in an amount of 0.01 to 2.0 g / m 2 Contains [1]~[ 4 ] A packaging material described in any one of the following. [ 6 ]The substrate has a Stockigt sizing degree of 20 seconds or more as measured in accordance with JIS P 8122:2004.[1] to [ 5 ] A packaging material described in any one of the following. [ 7 ][1]~[ 613. A packaging body obtained by thermally bonding at least a portion of the coating layer surface of the packaging material according to any one of claims 1 to 12. [Effects of the invention] Effect of the Invention
[0008] The packaging material of the present invention has good thermal adhesion, excellent oil resistance, and further has a small environmental impact. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In the present invention, "air permeability" is a value measured in accordance with JIS P 8117:2009. In the present invention, "Stöckigt sizing degree" is a value measured in accordance with JIS P 8122:2004. In the present invention, "peel strength" is a value measured in accordance with JIS P 8113:2006. In the present invention, "oil resistance" is a value measured in accordance with TAPPI UM-557. "~" indicating a numerical range means that the numerical values before and after it are included as the lower and upper limits.
[0010] One embodiment of the packaging material of the present invention is a packaging material including a substrate and a coating layer provided on at least one surface of the substrate. An undercoat layer may be provided between the coating layer and the substrate. In addition, the substrate may have a surface coated with a sizing agent.
[0011] The coating layer may be provided on only one surface of the substrate, or on one surface and the other surface opposite thereto. When the coating layer is provided on only one surface of the substrate, another layer may be provided on the other surface of the substrate.
[0012] The internal bond strength of the packaging material of the present invention measured according to JAPAN TAPPI 18-2 is 200 J / m 2 or more, preferably 300 J / m 2 More preferably, 500 J / m 2 More than 1000 J / m 2 That's all. By setting the internal bond strength of the packaging material to the above value, sufficient peel strength can be obtained at the heat-sealed portion.
[0013] In the case where the raw material of the substrate contains pulp, the method of controlling the internal bond strength of the packaging material includes setting the beating degree of the pulp slurry within a specific range and using a paper strength enhancer as an internal or external chemical. For the purpose of the present invention, it is more preferable to control the internal bond strength by beating the pulp slurry than to use a paper strength enhancer derived from a petrochemical material. The beating degree of the base pulp slurry in terms of Canadian Standard Freeness is not particularly limited, but is preferably, for example, 150 mLCSF or more and 500 mLCSF or less, more preferably 200 mLCSF or more and 450 mLCSF or less, and particularly preferably 200 mLCSF or more and 400 mLCSF or less.
[0014] The pulp beating method and beating device are not particularly limited, but for example, a double disc refiner (DDR) having high beating efficiency is preferably used. Examples of the paper strength enhancer used in the packaging material of the present invention include polyacrylamide resin, cationic starch, polyvinyl alcohol, styrene-butadiene latex, etc. These paper strength enhancers may be used alone or in combination of two or more. In particular, when a polyacrylamide resin paper strength agent is used, the amount used is not particularly limited, but it is preferable that the amount be approximately 0.1% to 5.0% by mass of the packaging material, more preferably 0.2% to 3.0% by mass, and even more preferably 0.2 to 1.0% by mass.
[0015] When the substrate is made of paper, the air permeability measured with an Oken type air permeability measuring device in accordance with JIS P 8117:2009 for packaging materials with the coating layer facing up is preferably 10 to 100,000 seconds, more preferably 50 to 100,000 seconds, and particularly preferably 100 to 50,000 seconds. By setting the air permeability by the above-mentioned measuring method within the above range, sealing inhibition at the adhesive interface due to evaporation of moisture contained in the paper substrate is unlikely to occur even when packaging materials are bonded together at high temperatures (170°C or higher), which is preferable. In addition, it can be used for applications requiring the gradual release of vaporized materials contained therein and the control of the inflow and outflow of air and moisture inside and outside the package, such as packaging materials for freshness-preserving agents and portable warmers. On the other hand, it is preferable to use a substrate having an air permeability of more than 100,000 seconds by the above-mentioned measuring method, because it is easy to obtain oil resistance.
[0016] The air permeability of the packaging material measured by the above-mentioned measurement method can be controlled by appropriately selecting the air permeability of the substrate measured by the above-mentioned measurement method, the coating amount of the paint for the coating layer (mass of the coating layer per unit area), the layer structure of the coating layer, coating and drying conditions, the beating degree of the pulp of the substrate, the basis weight and density of the substrate, etc., in the manufacturing method of the packaging material described below.
[0017] (base material) The raw materials used for the substrate are not particularly limited, but it is preferable to use pulp, regenerated cellulose fiber, biodegradable resin, plant-derived resin, etc., in order to reduce the environmental load. Examples of pulp include wood pulp and non-wood pulp. Examples of wood pulp include coniferous pulp and broadleaf pulp, and any of them may be used. In addition, the cooking method and bleaching method of wood pulp are not particularly limited. Examples of non-wood pulp include hemp pulp, kenaf pulp, bamboo pulp, cotton pulp, etc. These pulps may be used alone or in combination of two or more. Examples of regenerated cellulose fibers include rayon fiber, lyocell fiber, Bemberg fiber, etc.
[0018] Examples of biodegradable resins include polylactic acid, polybutylene succinate, polybutylene succinate adipate, and polybutylene succinate lactide. Examples of plant-derived resins include ethylene glycol produced from bioethanol, polyethylene terephthalate, polyolefin, and polyethylene furanoate produced from plant-derived monosaccharides and the like. The biodegradable resin and plant-derived resin may be formed into a film and used as a substrate, or may be formed into fibers and contained in the substrate.
[0019] The substrate can be obtained, for example, by making paper from a papermaking raw material containing a slurry in which a fibrous material such as pulp or resin fiber is dispersed in water.
[0020] The substrate can be obtained, for example, by making paper from a papermaking raw material containing a pulp slurry.
[0021] If necessary, various papermaking internal additives other than the above-mentioned paper strength agent can be added to the pulp slurry obtained by beating to prepare a papermaking raw material. It is also possible to mix the above-mentioned fibrous material into the pulp slurry. Examples of the internal additives include sizing agents, wet strength agents, aluminum sulfate, cationic starch, and other fixing agents. In addition to these, water retention agents, retention aids, defoamers, fillers, colorants, and other internal additives can be added to the papermaking raw materials as desired. These internal additives can be any of the known ones.
[0022] Examples of sizing agents include alkenyl succinic anhydride, alkyl ketene dimer, rosin compounds, etc. These sizing agents may be used alone or in combination of two or more. Among them, the use of rosin compounds derived from natural products is preferred because it increases the proportion of non-petrochemical materials used in the packaging material.
[0023] Examples of the wet strength agent include polyamide epoxy resin, epichlorine resin, and melamine resin. These wet strength agents may be used alone or in combination of two or more. The water-retaining agent may be, for example, carboxymethylcellulose. The filler may be, for example, talc, calcium carbonate, etc.
[0024] The substrate is coated with a styrene-(meth)acrylic acid copolymer compound and / or a styrene-maleic anhydride copolymer compound at a rate of 0.01 to 2.0 g / m on the side on which the coating layer is to be formed. 2 It is preferable to coat the coating material in the range of 100 to 200 mm.
[0025] The method of applying the undercoat layer can be to apply the above-mentioned styrene-(meth)acrylic acid copolymer compound or styrene-maleic anhydride copolymer compound alone or as a mixture with a binder such as starch to the base paper for the substrate obtained in the papermaking process using a size press or gate roll, which is a process subsequent to the papermaking process. Alternatively, the substrate can be formed by applying an undercoat agent containing a styrene-(meth)acrylic acid copolymer compound or a styrene-maleic anhydride copolymer compound to at least one surface of the substrate.
[0026] The sizing property of the substrate is preferably 20 seconds or more in terms of Stockigt sizing degree measured in accordance with JIS P 8122:2004, since this improves the heat sealability and oil resistance of the packaging material, more preferably 50 seconds or more, and even more preferably 100 seconds or more.
[0027] The basis weight of the substrate is, for example, 30 g / m to maintain the strength of the packaging material. 2 More than 40 g / m is preferable. 2 More preferably, 45 g / m 2 The above is even more preferable. The upper limit of the basis weight of the substrate is not particularly limited, but when used as a bag-shaped self-adhesive packaging material, it is, for example, 300 g / m 2 Less than 250 g / m is preferable. 2 Less than 200 g / m is more preferable. 2 The following is even more preferred:
[0028] The density of the substrate is, for example, 0.50 to 1.20 g / cm 3is preferably 0.65 to 1.10 g / cm 3 When the density of the substrate is equal to or higher than the lower limit, high adhesive strength is easily obtained at the heat-sealed portion, whereas when the density of the substrate is equal to or lower than the upper limit, sufficient breathability can be maintained.
[0029] (Coating layer) The coating layer of the present invention contains 30 to 100% by mass of casein and / or a salt thereof. By containing 30 to 100% by mass of casein and / or a salt thereof, excellent heat seal strength and oil resistance can be obtained. More preferably, the coating layer contains 50 to 100% by mass of casein and / or a salt thereof, and even more preferably, the coating layer contains 70 to 100% by mass of casein and / or a salt thereof.
[0030] Caseinates that can be used in the present invention are not particularly limited and can be obtained by acid precipitation from a liquid containing soluble casein (casein micelles) such as milk, and neutralization with a base such as a hydroxide (e.g., NaOH, KOH, Mg(OH)2, Ca(OH)2, NH4OH or a basic salt such as CaCO3, Na2CO3 or K2CO3 and mixtures thereof). The term caseinate also includes modified cases (e.g., glycated caseinate or deamidated caseinate).
[0031] Deamidated caseinates can be obtained, for example, by subjecting caseinate to the deamidating activity of an enzyme (e.g., deamidase or transglutaminase), in which some or all of the amide groups in the glutamine and / or asparagine side chains are deamidated to form carboxyl groups. Like casein, caseinates are composed of a mixture of four main casein types (alpha S1, alpha S2, bata and kappa casein).
[0032] However, (micellar) casein contains calcium and phosphate bound to the protein structure, stabilizing the micellar structure. Caseinate preparations may contain calcium or phosphate, but caseinate need not contain either calcium or phosphate. Of the caseinates, the sodium salt is preferred, as it is the more widely available.
[0033] The coating layer may further contain other components within the range that does not impair the effects of the present invention. The other components are not particularly limited, and may be any components that are generally used to impart heat sealability and oil resistance to packaging materials. Examples of the additives include organic pigments, inorganic pigments, waxes, metal soaps, antifoaming agents, dispersants, preservatives, water retention agents, and coloring dyes. Adding wax to the coating layer is preferable because it improves the coating suitability of the paint and makes it easier to form a uniform coating layer.
[0034] Deamidated caseinates can be obtained, for example, by subjecting caseinate to the deamidating activity of an enzyme (e.g., deamidase or transglutaminase), in which some or all of the amide groups in the glutamine and / or asparagine side chains are deamidated to form carboxyl groups. Like casein, caseinates are composed of a mixture of four main casein types (alpha S1, alpha S2, bata and kappa casein).
[0035] However, (micellar) casein contains calcium and phosphate bound to the protein structure, stabilizing the micellar structure. Caseinate preparations may contain calcium or phosphate, but caseinate need not contain either calcium or phosphate. Of the caseinates, the sodium salt is preferred, as it is the more widely available.
[0036] Examples of waxes include animal waxes, vegetable waxes, mineral waxes, petroleum waxes, synthetic waxes, etc., but for the purposes of the present invention, it is preferable to use animal waxes, vegetable waxes, and mineral waxes.
[0037] Examples of animal waxes include beeswax, shellac, whale wax, and wart wax. Examples of vegetable waxes include rice bran wax, soybean wax, palm wax, wood wax, and sunflower wax. Examples of mineral waxes include montan wax, ozokerite, ceresin, and oil shell.
[0038] Since the addition of animal wax or vegetable wax to the coating layer maintains the heat sealability and oil resistance of the resulting packaging material, the wax added to the coating layer is preferably an animal wax or vegetable wax, more preferably vegetable wax, and particularly preferably soybean-derived wax.
[0039] The amount of animal wax or vegetable wax used is not particularly limited, but is, for example, more than 0% by mass and 70% by mass or less of the coating layer. Alternatively, the mass ratio of casein to wax in the coating layer is preferably within the range of 100:0 to 30:70.
[0040] The mass of the coating layer per unit area is, for example, 0.1 to 30 g / m 2 and 0.3 to 20 g / m 2 and may be 1 to 10 g / m 2 and may be 3 to 10 g / m 2 It may be.
[0041] (Undercoat layer) Examples of the undercoat layer include the above-mentioned styrene-(meth)acrylic acid copolymer compound, styrene-maleic anhydride copolymer compound, and polyacrylamide resin, as well as various barrier layers, printed coating layers, and light-shielding layers.
[0042] (Back layer) In the present invention, a back layer can be provided as necessary. For example, various barrier layers, printed coating layers, light-shielding layers, etc. can be mentioned. Printing processing can be performed, and an overprint layer may be further provided on the printed layer.
[0043] (Manufacturing method of packaging materials) The packaging material is produced by forming a coating layer on at least one surface of a substrate. An example of a method for producing a packaging material is the following method A for producing a packaging material.
[0044] Packaging material manufacturing method A: A method for producing a packaging material, comprising the steps of applying a coating material for a coating layer to at least one surface of a substrate and drying the coating material, wherein the content of casein and / or a salt thereof in the coating material for the coating layer is 50 to 100% by mass of the total solid content of the coating layer.
[0045] The paint for the coating layer may be applied to only one surface of the substrate, or may be applied to both one surface and the other surface of the substrate. If necessary, the surface of the substrate may be smoothed before applying the coating material for the coating layer. After forming the thermal adhesive layer, the surface of the obtained heat seal sheet may be smoothed. The Oken smoothness of the surface of the substrate on which the coating layer is to be formed, as measured in accordance with JIS P 8155:2010, is preferably 30 to 5000 seconds, since this provides good adhesion during heat sealing and is less susceptible to adhesion inhibition due to an increase in air permeability, and is more preferably 50 to 3000 seconds.
[0046] The method for applying the coating material for the coating layer is not particularly limited, and various known wet application methods can be used. For example, it can be applied using an on-machine size press device of a papermaking machine, a transfer roll coater (such as a shim sizer or gate roll coater), a spray device, etc. Off-machine application can be performed using a general coating device, such as a blade coater, an air knife coater, a roll coater, a reverse roll coater, a shim sizer, a gate roll coater, a bar coater, a curtain coater, a slot die coater, a gravure coater, a champlex coater, a brush coater, a two-roll coater, a bill blade coater, a short dwell coater, etc. Application can also be performed using a printing machine such as a gravure printing machine or a flexographic printing machine.
[0047] The device for drying the applied coating layer paint may be a cylinder dryer that comes into contact with the coating surface, but from the viewpoint of preventing contamination of the device, an air dryer, an infrared heater, or the like that does not come into contact with the coating surface is preferred. Considering operability and productivity, the application and drying of the coating layer paint is preferably performed on-machine. The type of paper machine used to make the substrate is not particularly limited, and examples include a Fourdrinier paper machine, a short wire paper machine, a cylinder paper machine, a tilt paper machine, etc. An on-machine type paper machine equipped with a coating device and a dryer is preferred.
[0048] The drying conditions after application of the coating layer paint include, for example, conditions of 60 to 160° C. and 20 seconds to 5 minutes.
[0049] (Action and effect) The packaging material is capable of packaging the contents by self-adhesive or by adhering to other materials using a heat seal method. The adhesive strength of the heat-sealed portion can be measured by cutting a test piece into a width of 15 mm, which is heat-sealed by applying heat and pressure so that the coating layers of the packaging material are in contact with each other, and peeling it at a peeling speed of 300 mm / min using a tensile tester according to JIS P 8113: 2006 using the 180 degree peel method. Alternatively, the adhesive strength can be measured in the same way for packaging materials and other materials. The peel strength is preferably 0.5 N / 15 mm or more, more preferably 1.0 N / 15 mm or more, further preferably 2.0 N / 15 mm or more, and most preferably 5.0 N / 15 mm or more.
[0050] Furthermore, the packaging material can also exhibit oil resistance. The oil resistance can be evaluated by dropping kit liquid of each grade prepared according to TAPPI UM-557 onto the coating surface of the coating layer and checking whether stains appear after 15 seconds. The oil resistance (kit) is preferably grade 2 or higher, more preferably grade 5 or higher, even more preferably grade 8 or higher, and most preferably grade 10 or higher. EXAMPLES
[0051] The present invention will be specifically described below with reference to examples. Note that the present invention is not limited to these examples. Note that, unless otherwise specified, % is mass % and parts is mass parts. Measurement and evaluation methods used in each example are shown below.
[0052] [Measurement of internal bond strength] The internal bond strength of the packaging material was measured using an I-BOND PREP STATION (Model 80-01, manufactured by Testing Machines Co., Ltd.) in accordance with JAPAN TAPPI 18-2.
[0053] [Oken air permeability measurement] The Oken air permeability of the substrate and packaging material was measured in accordance with JIS P 8117: 2009. The air permeability of the substrate was measured with the surface on which the coating layer was to be provided facing up, and the air permeability of the packaging material was measured with the surface on which the coating layer was to be provided facing up.
[0054] [Peel test] The packaging materials were stacked so that the coated surfaces were in contact with each other, and then heat-pressed using a heat press tester under heat-pressing conditions of 150°C, 0.2 MPa, and 1.0 second to produce a heat-pressed product. The heat-pressed product prepared by the above method was cut to a width of 15 mm to prepare a sample for measuring peel strength. The peel strength (N / 15 mm) of the obtained sample for measuring peel strength was measured in accordance with JIS P 8113:2006 using a tensile tester (model: Tensilon RTC-1250A, manufactured by Orientec Co., Ltd.) by chucking the ends of the composite film and heat seal sheet of the sample and peeling them at a peel speed of 300 mm / min using the 180° peel method. The higher the peel strength, the better the thermal adhesion.
[0055] [Oil resistance of coating layer surface] Each grade of kit liquid, prepared in accordance with TAPPI UM-557, was dropped onto the coating surface of the packaging material, and the coating was evaluated based on whether stains occurred after 15 seconds.
[0056] <Example 1> (Manufacture of substrate) Hardwood bleached kraft pulp (LBKP) was beaten in a DDR to a Canadian standard freeness (freeness) of 320 mL as described in JIS P 8121-2:2012 to obtain a pulp slurry. The pulp slurry was added with the following internal chemicals based on the pulp mass: 1.0% aluminum sulfate on an absolute dry basis, 0.05% alkenyl succinic anhydride sizing agent (Fibran 81K, manufactured by Arakawa Chemical Industries Co., Ltd.) previously dispersed with cationic starch (Pillar 3YK, manufactured by Pillar Starch Co., Ltd.), 0.7% amphoteric polyacrylamide resin paper strength enhancer (PAM) (trade name: Polystron OFT-3, manufactured by Arakawa Chemical Industries Co., Ltd., mass average molecular weight 3 million), and 0.4% epichlorine resin wet paper strength enhancer, to obtain a papermaking raw material. The raw material for papermaking was made into paper using a fourdrinier papermaking machine, dried using a cylinder dryer, and then 40 g / m2 of a 6.0% by mass solution of hydrophobic starch (product name: GRS-T110, manufactured by Oji Cornstarch Co., Ltd.) and a styrene-acrylic acid copolymer surface sizing agent (product name: Polymaron E-109, manufactured by Arakawa Chemical Industries Co., Ltd.) mixed at a solid ratio of 95:5 was pressed into a size press in an online process. 2 After coating, the substrate was dried in a cylinder dryer to obtain a substrate. The basis weight of the substrate obtained was 120 g / m 2 , density is 0.74g / cm 3 The Oken air permeability was 23 seconds, the Oken smoothness was 16 seconds for the felt side (the side on which the coating layer was formed) and 11 seconds for the wire side, and the Stockigt sizing degree was 117 seconds.
[0057] (Casein dissolution) 550 parts by mass of water was heated, and when it reached 45°C, 30 parts by mass of 25% by mass ammonia was added. After further heating to 50°C, 125 parts by mass of casein was added and stirred to dissolve the casein. After dissolution, the casein was diluted with adjusted water to obtain a 10% by mass casein solution.
[0058] (Preparation of coating layer paint) The 10% by mass of casein obtained by dissolving the casein above was diluted with water to 7.0% by mass to obtain a coating layer paint. The viscosity of the resulting coating layer paint at 7.0% by mass was 45 mPa s as measured by a Brookfield viscometer.
[0059] (Manufacturing of packaging materials) The coating layer paint was applied to the F side of the substrate obtained above using a bar coater, and then dried in a blower dryer at 110°C for 2 minutes to form a thermal adhesive layer. Here, the coating amount of the thermal adhesive layer paint after drying was 3.3 g / m 2 In this way, a packaging material was obtained.
[0060] <Example 2> (Dissolution of sodium caseinate) 150 parts by mass of sodium caseinate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dispersed in 850 parts by mass of water, heated to 90°C with stirring, and then held at 90°C for 30 minutes. The mixture was then cooled and diluted with adjusted water to obtain a 10% by mass sodium caseinate solution.
[0061] (Preparation of coating layer paint) In preparing the coating layer paint of Example 1, 160 parts by mass of water and 10% by mass of sodium caseinate obtained by dissolving the sodium caseinate above were diluted with water to 7.0% by mass to obtain a coating layer paint. The viscosity of the obtained coating layer paint at 7.0% by mass was 50 mPa s as measured by a B-type viscometer.
[0062] (Manufacturing of packaging materials) The coating layer paint was applied to the F side of the substrate using a bar coater, and then dried in a blower dryer at 110°C for 2 minutes to form a thermal adhesive layer. Here, the coating amount of the thermal adhesive layer paint after drying was 3.3 g / m 2 In this way, a packaging material was obtained.
[0063] <Example 3> A packaging material was obtained in the same manner as in Example 1, except that in the production of the substrate of Example 1, the bleached hardwood pulp was beaten to a Canadian standard freeness of 180 mL, and the alkenyl succinic anhydride sizing agent, the amphoteric polyacrylamide resin-based paper strength agent, and the epichlorine resin wet strength agent, which had been dispersed in advance with cationic starch, were not added, and instead 0.9 mass% of a rosin sizing agent (product name: Sizepine N111-50, manufactured by Arakawa Chemical Industries Co., Ltd.) was used. The basis weight of the obtained substrate was 120 g / m 2 , density is 0.74g / cm 3 The Oken air permeability was 116 seconds, the Oken smoothness was 16 seconds for the felt side (the side on which the coating layer was formed) and 11 seconds for the wire side, and the Stockigt sizing degree was 123 seconds.
[0064] <Example 4> A packaging material was obtained in the same manner as in Example 1, except that no coating was performed using a size press device in the production of the substrate in Example 1. The basis weight of the substrate obtained above was 117.6 g / m2, the density was 0.74 g / cm3, the Oken air permeability was 23 seconds, the Oken smoothness was 16 seconds for the felt surface and 11 seconds for the wire surface, and the Stockigt sizing degree was 25 seconds.
[0065] <Example 5> Instead of the substrate in Example 1, a 20 μm-thick biodegradable polylactic acid film (Palgreen BO, manufactured by Mitsui Chemicals Tohcello Co., Ltd.) was coated on one side with a coating layer paint at a dry weight of 3.3 g / m 2 A packaging material was obtained in the same manner as in Example 1, except that the above was applied and dried.
[0066] <Example 6> (Manufacture of substrate) To 100 parts by mass of bleached hardwood kraft pulp (freeness as defined in JIS P 8121-2:2012: 420 mLcsf), 0.09 parts by mass of a rosin-based emulsion sizing agent (product name: AL-1200, manufactured by Nippon PMC Co., Ltd.), 3.5 parts by mass of aluminum sulfate, 0.2 parts by mass of a starch-grafted acrylamide-based paper strength agent (product name: DG4204, manufactured by Nippon PMC Co., Ltd.), 0.03 parts by mass of a release agent (product name: Meikatex HP-68C, manufactured by Meisei Chemical Industry Co., Ltd.), and 0.6 parts by mass of a cationized starch (product name: Ace K-100, manufactured by Oji Corn Starch Co., Ltd.) were added, and the mixture was made into paper using a known Fourdrinier papermaking machine equipped with a Yankee dryer to obtain a paper having a basis weight of 65 g / m. 2 The density of the resulting single-sided glazed paper was 0.81 g / cm 3 The Oken smoothness of the glossy side measured according to JIS P 8155:2010 was 320 seconds for the glossy side and 10 seconds for the rough side. The air permeability of the obtained one-sided glossy paper measured according to JIS P 8117:2009 was 46 seconds. The Stockigt sizing degree was 27 seconds.
[0067] (Manufacturing of packaging materials) Instead of the substrate used in Example 1, the coating layer paint was applied to the glossy surface of the substrate obtained in the above "Production of substrate" using a bar coater, and the substrate was dried in a blower dryer at 110°C for 2 minutes to form a thermal adhesive layer. Here, the coating amount of the thermal adhesive layer paint after drying was 3.3 g / m 2 In this way, a packaging material was obtained.
[0068] <Example 7> (Preparation of coating layer paint) A coating paint was obtained by mixing and stirring 800 parts by weight of a 10.0% by weight casein aqueous solution, 67 parts by weight of a 30.0% by weight soybean-derived wax (Eurika Coat SW166N, EURIKAS), and 562 parts by weight of water. The viscosity of the resulting coating paint at 7.0% by weight was 25 mPa s measured with a B-type viscometer.
[0069] (Manufacturing of packaging materials) Instead of the coating layer paint used in Example 6, the coating layer paint obtained in the above "Preparation of coating layer paint" was applied to the glossy surface of the substrate at a coating amount of 3.3 g / m 2 A packaging material was obtained in the same manner as in Example 6, except that the coating was performed so that the thickness of the coating film was 100 μm.
[0070] <Example 8> (Preparation of coating layer paint) A coating paint was obtained by mixing and stirring 400 parts by weight of a 10.0% by weight casein aqueous solution, 200 parts by weight of a 30.0% by weight soybean-derived wax (Eurika Coat SW166N, EURIKAS), and 829 parts by weight of water. The viscosity of the resulting coating paint at 7.0% by weight was 16 mPa s measured with a B-type viscometer.
[0071] (Manufacturing of packaging materials) Instead of the coating layer paint used in Example 7, the coating layer paint obtained in the above "Preparation of coating layer paint" was applied to the glossy surface of the substrate at a coating amount of 3.3 g / m 2 A packaging material was obtained in the same manner as in Example 7, except that the coating was performed so that the thickness of the coating film was 100 μm.
[0072] <Comparative Example 1> (Preparation of coating layer paint) A coating paint was obtained by mixing and stirring 200 parts by weight of a 10.0% by weight casein aqueous solution, 267 parts by weight of a 30.0% by weight soybean-derived wax (Eurika Coat SW166N, EURIKAS), and 962 parts by weight of water. The viscosity of the resulting coating paint at 7.0% by weight was 8 mPa s measured with a B-type viscometer.
[0073] (Manufacturing of packaging materials) Instead of the coating layer paint used in Example 7, the coating layer paint obtained in the above "Preparation of coating layer paint" was applied to the glossy surface of the substrate at a coating amount of 3.3 g / m 2 A packaging material was obtained in the same manner as in Example 7, except that the coating was performed so that the thickness of the coating film was 100 μm.
[0074] <Comparative Example 2> (Manufacture of substrate) To a pulp slurry of unbeaten bleached hardwood kraft pulp (LBKP, Canadian standard freeness (freeness) specified in JIS P 8121-2:2012 is 520 mL), 1.0% aluminum sulfate on an absolute dry basis and 0.05% alkenyl succinic anhydride sizing agent (Fibran 81K, manufactured by Arakawa Chemical Industries Co., Ltd.) previously dispersed with cationic starch (Pillar 3YK, manufactured by Pillar Starch Co., Ltd.) were added as internal chemicals relative to the mass of pulp to obtain a papermaking raw material. The papermaking raw material was made into paper on a Fourdrinier papermaking machine and dried in a cylinder dryer. In the online process, a 6.0 mass% solution of a mixture of hydrophobic starch (trade name: GRS-T110, manufactured by Oji Cornstarch Co., Ltd.) and a styrene-acrylic acid copolymer surface sizing agent (trade name: Polymeron E-109, manufactured by Arakawa Chemical Industries Co., Ltd.) in a solid ratio of 95:5 was added to a size press device at 40 g / m. 2 After coating, the substrate was dried in a cylinder dryer to obtain a substrate. The basis weight of the substrate obtained was 120 g / m 2 , density is 0.74g / cm 3 The Oken air permeability was 15 seconds, the Oken smoothness was 16 seconds for the felt surface (the surface on which the coating layer was formed) and 11 seconds for the wire surface, and the Stockigt sizing degree was 102 seconds.
[0075] (Manufacturing of packaging materials) Instead of the substrate used in Example 1, the coating layer paint was applied to the F side of the substrate obtained in the above "Production of substrate" using a bar coater, and the substrate was dried in a blower dryer at 110°C for 2 minutes to form a thermal adhesive layer. Here, the coating amount of the thermal adhesive layer paint after drying was 3.3 g / m 2 In this way, a packaging material was obtained.
[0076] <Evaluation> The packaging materials of Examples 1 to 8 and Comparative Examples 1 and 2 were subjected to the following evaluations. The results are shown in Table 1.
[0077] [Table 1]
[0078] As shown in the above results, the packaging materials of Examples 1 to 8 had a heat seal strength of 1.20 N / 15 mm or more in the peel test, and also had a Kit oil resistance of grade 5 or more. On the other hand, the packaging material of Comparative Example 1 had sufficient heat seal strength, but the Kit oil resistance was grade 2, raising concerns about problems in use. The heat seal strength of Comparative Example 2 was 0.30 N / 15 mm, which may cause problems in use, such as accidental opening. [Industrial Applicability]
[0079] The packaging material of the present invention is an excellent packaging material that has sufficient heat sealability and oil resistance, and has a small environmental impact because it is mainly made of non-petrochemical materials.
Claims
1. A packaging material having a coating layer on at least one side of a substrate, the coating layer containing 30 to 100% by mass of casein and / or a salt thereof, and the internal bond strength of the packaging material measured in accordance with JAPAN TAPPI 18-2 is 200 J / m 2 That's all. The substrate is obtained by making a papermaking raw material containing a slurry in which a fibrous material is dispersed in water, The packaging material has an Oken air permeability of 3360 seconds or more measured in accordance with JIS P 8117:2009.
2. The packaging material according to claim 1 , wherein the coating layer contains a wax.
3. 3. The packaging material according to claim 1, wherein the base material is made of wood pulp.
4. 4. The packaging material according to claim 3, wherein the wood pulp has a beating degree according to Canadian Standard Freeness of 150 mLCSF or more and 500 mLCSF or less.
5. The substrate is coated with a styrene-(meth)acrylic acid copolymer compound and / or a styrene-maleic anhydride copolymer compound at a rate of 0.01 to 2.0 g / m on the side on which the coating layer is to be formed. 2 The packaging material according to any one of claims 1 to 4, which is coated.
6. The packaging material according to any one of claims 1 to 5, wherein the substrate has a Stockigt sizing degree of 20 seconds or more as measured in accordance with JIS P 8122:2004.
7. A package obtained by thermally bonding at least a part of the coating layer surface of the packaging material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Modified thixotropic agent and sealant containing same
CN112210317A
Improvements in or relating to the production of heat-sealable, transparent, cellulosic sheets and films
GB741500A
JP1973026268A
Water-based adhesive
JP1988258976A
Edible film
JP1990312555A